THE IMPACT OF RISK AND REPUTATION ON FINANCIAL PERFORMANCE IN ISLAMIC BANKING: EVIDANCE FROM INDONESIA - Falikhatun Falikhatun; Mutiarafah Mutiarafah (Univeristas Islam Bandung, 2021)
This study aims to examine the impact of risk and reputation on financial performance. More specifically, we use financing risk, liquidity risk, reputation with rewards, and growth in profit-sharing based financing as our variable of interests. We also assign bank size as a control variable. Our data is analyzed using Generalized Least Square (GLS) regression. Islamic Commercial Banks listed in Sharia Banking Statistics (Statistik Perbankan Syariah - SPS) published by OJK in 2015−2019 are selected as our sample. We find that (1) financing risk has a negative effect on financial performance; and (2) both reputation with rewards and bank size have a positive effect on financial performance. However, liquidity risk and growth in profit-sharing based financing do not affect financial performance. Several research implications are the importance of risk mitigation, the importance to maintain the reputation of the Islamic bank’s stakeholders, and creating innovative funding and financing products.